2011
DOI: 10.1097/ta.0b013e318213faf1
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Embolization of Nonvariceal Upper Gastrointestinal Bleeding: Predictors of Clinical Failure

Abstract: AE clinical failure portends poor prognosis. Caution should be exercised when considering AE, particularly AE using coils, in patients with a history of anticoagulant, corticosteroid, or vasopressor use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
9
2
Order By: Relevance
“…The use of anticoagulant or antiplatelet medication has been shown to be a significant risk factor for clinical failure in UGI bleeding (33), but this study found no statistically significant association between anticoagulant or antiplatelet medication and clinical success rate. The patients who had taken anticoagulant or antiplatelet medication only had a slightly lower clinical success rate than patients who had not taken these medications.…”
Section: Discussioncontrasting
confidence: 82%
“…The use of anticoagulant or antiplatelet medication has been shown to be a significant risk factor for clinical failure in UGI bleeding (33), but this study found no statistically significant association between anticoagulant or antiplatelet medication and clinical success rate. The patients who had taken anticoagulant or antiplatelet medication only had a slightly lower clinical success rate than patients who had not taken these medications.…”
Section: Discussioncontrasting
confidence: 82%
“…Our findings complement those of a recent study providing additional insights into the short-term outcomes of angiographic therapy and subsequent embolization in patients with GIB. [11][12][13] Management options for patients with acute nonvariceal upper GIB that does not respond to initial endoscopic treatment include repeat endoscopy, emergency surgery, and angiographic embolization. Several studies have compared the effectiveness of surgery to embolization in treating patients with GIB.…”
Section: Discussionmentioning
confidence: 99%
“…19 The need for surgical intervention for patients with clinically unsuccessful arterial embolization is 15 to 20%. 19,30 One study found UGIB to be more resistant to hemostasis (with a higher rate of early rebleeding) than lower GI hemorrhage. 18 This was hypothesized to be secondary to refilling of injured vessels through collateral circulation distal to the point of embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with clinical failure of arterial embolization include the use of anticoagulants, underlying coagulopathy, longer time interval between onset of bleed and embolization, increased number of pRBC transfusions, hypovolemic shock and/or vasopressor use, corticosteroids, and the use of coils as the lone embolic agent. 18,19,30,31 The overall postembolization complication rate is 6 to 9%. 30 Complications include access site hematoma, arterial dissection, contrast nephropathy, and nontarget embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation